2008
DOI: 10.1016/j.jpeds.2008.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Biomarkers of Bone Metabolism in Children: Impact of Growth Velocity and Body Size in Healthy Children and Chronic Disease

Abstract: Objectives-To determine the effects of growth, maturation, and whole body bone mineral content (WB-BMC) accrual on biomarkers of bone formation [bone specific alkaline phosphatase (BSAP)] and resorption [urine deoxypyridinoline/creatinine (DPD)] in healthy children and children with Crohn's disease.Study design-BSAP and DPD were measured at baseline, and growth and dual energy x-ray absorptiometry (DXA) WB-BMC were measured at baseline and six months in 202 controls and 110 subjects with Crohn's disease, ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 32 publications
5
60
1
1
Order By: Relevance
“…Our results showed that the levels of all biochemical bone markers in both patients and controls were highest in the preearly-pubertal years, followed by an overall decrease through puberty and postpubertal years, in accordance with other studies of bone markers in children, adolescents, and adults (12,(15)(16)(17)(18)(19). Previously, bone marker values have been shown to increase during early-mid puberty (Tanner breast developmental stages 2 and 3), corresponding to increasing height velocity (15,17,18).…”
Section: Rett Syndrome and Low Bone Turnoversupporting
confidence: 92%
See 3 more Smart Citations
“…Our results showed that the levels of all biochemical bone markers in both patients and controls were highest in the preearly-pubertal years, followed by an overall decrease through puberty and postpubertal years, in accordance with other studies of bone markers in children, adolescents, and adults (12,(15)(16)(17)(18)(19). Previously, bone marker values have been shown to increase during early-mid puberty (Tanner breast developmental stages 2 and 3), corresponding to increasing height velocity (15,17,18).…”
Section: Rett Syndrome and Low Bone Turnoversupporting
confidence: 92%
“…Generally, bone markers are known to be related to changes in bone remodeling and in bone mass in elderly postmenopausal women (23,25) but not in young premenopausal women (28). Studies of the association between markers of bone turnover and subsequent bone gain in healthy girls have shown conflicting results (15,17,22,29). An association between bone markers and bone gain should be examined prospectively in a larger group of patients with RTT of different ages and pubertal stages.…”
Section: Rett Syndrome and Low Bone Turnovermentioning
confidence: 99%
See 2 more Smart Citations
“…During remodeling, which is seen in adults, bone formation and resorption are tightly coupled. In contrast, bone modeling during growth in children results in new bone formation at a different site than the site of resorption and at a faster rate, leading to alterations in bone shape and bone mass accrual [13]. Interpretation of biochemical markers of bone turnover [bone turnover markers (BTMs)] in children is therefore more challenging than that in adults as biomarkers of bone metabolism represent the combined effects of bone formation, skeletal growth and bone remodeling.…”
Section: Introductionmentioning
confidence: 99%